Is there a gender effect on the cost of bank financing? - Mascia, Danilo V.; Rossi, Stefania P.S. (Elsevier, 2017)
In this paper, we address the question of whether the gender of a firm’s leader affects the cost of bank funding faced by small and medium enterprises in Europe. Using a large sample of observations of non-financial firms, during the years 2009-2013, we empirically test for the presence of discrimination, comparing female-led and male-led firms. After controlling for a rich set of variables and addressing potential endogeneity, our results show that i) female-led enterprises are more likely to face worse price conditions for bank financing compared to their male-led counterparts and, ii) firms whose leadership changes from female to male are more likely to benefit from an improvement in interest rate levels. This evidence is robust to different model specifications and various methodological approaches. The existence of such bias in the credit markets highlights the need of policy measures addressing female-led businesses, thus reducing their bank financing burdens and enhancing their entrepreneurial opportunities.